Length–weight relationships of the tropical cephalopod Uroteuthis chinensis (Gray, 1849) from Sabah, Malaysia - Siddique, Mohammad Abdul Momin; Arshad, Aziz; Sarker, Mohammad Nurul Amin (Taylor & Francis, 2014)
This study focuses on the length–weight relationships (LWR) and the relative condition factor (Kn) of Uroteuthis chinensis from the Marudu Bay, Malaysia. The mean mantle length (±SE) and the total body weight (±SE) of U. chinensis were 29.02 ± 1.31 mm and 3.37 ± 0.46 g, respectively. The calculated growth coefficient b was 2.579, which indicated the hypoallometric growth of the animals from the study area. The study also showed that the dorsal mantle length and the total body weight were highly correlated (r = 0.930, p < 0.001). The mean values of the relative condition factor (Kn) of U. chinensis were found to be 1.0062 ± 0.1134. To our knowledge, the LWR and condition indices of U. chinensis collected from the Marudu Bay presented herein represent the first reference available to Malaysian waters.